A Case of Primary JC Polyomavirus Infection–Associated Nephropathy. Issue 12 (30th October 2014) - Lautenschlager, I.; Jahnukainen, T.; Kardas, P.; Lohi, J.; Auvinen, E.; Mannonen, L.; Dumoulin, A.; Hirsch, H. H.; Jalanko, H.
<x xml:space="preserve">Abstract</x> A 15‐year‐old boy with a posterior urethral valve received a deceased donor kidney transplant (KT) in March 2011. Basiliximab induction followed by tacrolimus‐based triple medication was used as immunosuppression. Eleven months after KT, the graft function deteriorated and the biopsy demonstrated interstitial nephritis suggestive of acute rejection. BK polyomavirus (BKPyV) surveillance in urine and plasma was negative. The patient received methylprednisolone pulses and anti‐thymocyte globulin. Immunohistochemistry was positive for simian virus 40 (SV40) large T‐antigen (LTag) in the biopsies, and quantitative polymerase chain reaction for JC polyomavirus (JCPyV) indicated high viral loads in urine and borderline levels in plasma. Immunosuppression was reduced and follow‐up biopsies showed tubular atrophy and interstitial fibrosis. Two years after KT, antibody‐mediated rejection resulted in graft loss and return to hemodialysis. Retrospective serologic work‐up indicated a primary JCPyV infection with seroconversion first for IgM, followed by IgG, but no indication of BKPyV infection. In the SV40 LTag positive biopsies, JCPyV deoxyribonucleic acid (DNA) with archetype noncoding control region was detected, while BKPyV DNA was undetectable. To the best of our knowledge, this is the first reported case of primary JCPyV infection as the cause of PyV‐associated nephropathy in KT.